Three types of organizational boundary spanning: Predicting CSR policy extensiveness among global consumer products companies. (10th February 2020) - Lim, Alwyn; Pope, Shawn
Abstract: As part of the rise of a worldwide corporate social responsibility (CSR) movement, companies have increasingly incorporated social and environmental concerns into their policies. This paper examines the extensiveness of these policies, proposing that an underappreciated contributor is the degree of organizational boundary spanning. The paper is novel in integrating multiple types of boundary spanning into a single empirical framework, including product, sub‐unit, and national boundary spanning. The paper adds complexity to the literature by theorizing that different types of boundary spanning associate with CSR policy extensiveness in different issue areas. The results show that product spanning associates with CSR policy extensiveness in the area of consumers, sub‐unit spanning in the areas of workers, and nation‐state spanning in all issue areas. A unique, comprehensive, and global data set of 2, 714 prominent consumer goods companies in the GoodGuide database underpins these findings.